HUBUNGAN KANDUNGAN KAROTENOID DAN RETINOL DALAM DARAH DAN ASI PADA IBU MENYUSUI DI DAERAH PENGHASIL DAN BUKAN PENGHASIL SAYURAN - Joko Pambudi; Fitrah Emawati; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2001)
Association of Carotenoids and Retinol Levels In Blood and Breastmilk of Breastfeeding Mothers In Vegetables Producing Area and Non-Vegetables Producing Area.Background: Vegetables are available in abundant amount in the less developed countries, including Indonesia, and are the source of carotenoids and other important nutrient, especially vitamin A. In rural areas, vegetables are becoming important source of vitamin A, especially for breastfeeding mothers.Objectives: To study carotenoids and retinol levels in blood and breastmilk of breastfeeding mothers in vegetables producing area and non-vegetables producing area, and its implication to the availability of vitamin A to breastfeeding mothers.Method: Samples were collected from 87 breastfeeding mothers with their breastfeeding age of 3-6 months, and they came from two areas, vegetables producing area and non-vegetables producing area. Blood and breastmilk were taken and analyzed for their carotenoids and retinol levels using HPLC.Results: The study found there were differences of carotenoids components and retinol in blood and breastmilk of breastfeeding mothers between vegetables producing area and non-vegetables producing area. The levels of lutein, lycopene, β-carotene and retinol in blood of breastfeeding mothers living in vegetables producing area were significantly different (p<0.01) from non vegetables producing area. However, for β-cryptoxanthin, and α-carotene were not significantly different (p>0.05). The levels of carotenoids and retinol in breastmilk showed differences. The levels of lutein, lycopene, α-carotene, β-cryptoxanthin and retinol in breastmilk of mothers in vegetables producing area were significantly different (p<0.01) from non-vegetables producing area. While β-carotene level was not significantly different (p>0.05). There were a correlation of lutein (r=0.4610, p<0.05), β-cryptoxanthin (r=0.3321, p<0.05), and β-carotene (r=0.4548, p<0.05) levels between in blood and breastmilk in vegetables producing area. While only level of lutein (r=0.6166, p<0.01) in blood correlated with breastmilk in non-vegetables producing area. There was no strong correlation (p>0.05) between vegetables consumption and carotenoids and retinol levels of blood and breastmilk, botj in vegetables producing  area and non-vegetables producing area.Conclusion: The result of study showed carotenoids and retinol levels of blood and breastmilk in mothers from vegetables producing area were higher than that of non-vegetables producing area.Recommendation: To encourage breastfeeding mothers in order to consume more vegetables intensively through the existing program.Keywords: carotenoids, Lutein, β-cryptoxanthin, lycopene, β-carotene, retinol, α-carotene.